Synthesis and Characterization of 3 - Substituted Coumarin (Baghdad Science Journal, 2016)
The reaction of(2-oxo-2H-chromen-3-Carbonyl chloride)(k1) with hydrazine in boiling ethanol gives the hydrazide(K2).When compound (k2) reacts with various aromatic aldehydes ,the corres ponding Schiff bases(k3–k4) achieve new series of thiazotidines (k5–k6) and azetidinones (k7–k8) obtained from the reactions of appropriate Schiff bases with mercapto acetic acid and chloro acetyl chloride respectively. All the compounds are characterized by FT-IR,1H-NMR and GC-Ms.